2001
DOI: 10.1021/ol010003w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electronic Spectra, and Crystal Structural Properties of Fluorinated [33](1,3,5)cyclophanes

Abstract: [structure: see text] Trifluoro- and hexafluoro[3(3)](1,3,5)cyclophanes 3 and 4 were synthesized with TosMIC coupling as a key reaction. The pi-pi absorption bands show blue shifts as the number of fluorine atoms is increased. In the crystalline state, characteristic stacking with the fluorinated benzene rings facing each other is observed in both cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Therefore, the fluorine substitution modifies crystal structure of the azacyclophane system. Such effects of fluorine substitution on crystal structures have also been reported for [3 3 ]cyclophane system …”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, the fluorine substitution modifies crystal structure of the azacyclophane system. Such effects of fluorine substitution on crystal structures have also been reported for [3 3 ]cyclophane system …”
Section: Resultssupporting
confidence: 63%
“…Thus, it would be of interest to reveal the substituent effects on the photochemical behavior. It has been reported that introduction of fluorine atoms into aromatic cores of [3 3 ]cyclophanes significantly affected the electronic features of the carbon‐bridged cyclophane, thus, electronic absorption band of hexafluoro[3 3 ](1,3,5)cyclophane remarkably blue shifted compared to that of nonsubstituted parent cyclophane . Fluorination on the side chains may modify photochemical properties of a cyclophane system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3a] In the crystal packing diagram of the [3 n ]CPs, neighboring cyclophane molecules are arranged in an orthogonal fashion, [3] whereas the 5,7, 9-trifluoro-and 5,7,9,14,16,18-hexafluoro[3 3 ] (1,3,5)CPs are stacked with the fluorinated benzene rings facing each other, with the repeated stacking forming a column in the solid state. [4] We have modified the [3 3 ](1,3,5)CP skeleton in order to study the donor (D)Ϫacceptor (A) interaction in the solid state in more detail. We chose 5,7,9-trimethyl[3 3 ](1,3,5)CP 1 as a donor with two binding sites of different donating ability, as well as 2,11,20-trithia[3 3 ](1,3,5)CP 4 [5] and 1,3,10,12,19,21-hexathia[3 3 ](1,3,5)CP 5 [6] as donors with enhanced intermolecular interactions in the crystal packing.…”
Section: Introductionmentioning
confidence: 99%
“…Koga et al[66] have investigated the electronic spectra of a series of fluoro[3 3 ] (1,3,5)cyclophanes(63)(64)(65) along with the parent 66 as a reference in chloroform.The p-p* absorption bands show blue shifts as the number of fluorine atoms is increased. Although in 63 the longest-wavelength band (k max = 313 nm, lg e = 2.53) suffers a slight red shift compared with that of 66 (k max = 308 nm, lg e = 1.94), the band shows a gradual blue shift as the number of fluorine atoms increases: 64 (k max = 296 nm, lg e = 1.93), 65 (k max = 291 nm, lg e = 2.27).…”
mentioning
confidence: 99%